Sequence of Electrocardiographic and Acoustic Cardiographic Changes and Angina during Coronary Occlusion and Reperfusion in Patients Undergoing Percutaneous Coronary Intervention - Lee, Eunyoung (Ann Noninvasive Electrocardiol, 2009)
Background: Previous studies have suggested that ventricular function may be impaired without or prior to electrocardiographic changes or angina during ischemia. Understanding of temporal sequence of electrical and functional ischemic events may improve the detection of myocardial ischemia. Methods: A prospective study was performed in 21 subjects undergoing percutaneous coronary intervention (PCI) who had both ST amplitude changes >2 standard deviations above baseline on 12‐lead electrocardiography (ECG), and new or increased third or fourth heart sound (S3 or S4) intensity measured by computerized acoustic cardiography. The sequence of the onset and resolution of these signs of ischemia were examined following coronary balloon inflation and deflation. Results: Electrocardiographic ST amplitude and diastolic heart sound changes occurred contemporaneously, shortly after coronary occlusion (mean onset from balloon inflation; ST changes, 21 ± 17 seconds; S4, 25 ± 26 seconds; S3, 45 ± 43 seconds). In 40% of patients, a new or increased S3 or S4 developed earlier than ST changes. Anginal symptoms occurred in only 2 of the 21 subjects during ischemia with a mean onset time of 68 seconds. ST‐segment changes resolved earliest (33 seconds after balloon deflation) while diastolic heart sounds (89 ± 146 seconds) and angina (586 ± 653 seconds) resolved later. Conclusion: A new or intensified S3 and/or S4 occurred contemporaneously with electrocardiographic changes during ischemia. These diastolic heart sounds persisted longer than ST changes following coronary reperfusion. Acoustic cardiographic assessment of diastolic heart sounds may aid in the early detection of myocardial ischemia, particularly in those patients with an uninterpretable ECG.